Group Work in the English Language Curriculum - Chappell, P. author. aut Link
XII, 212 p.
Keywords: This book explores how using small groups in second language classrooms supports language learning. Chappell's experience as a language teacher equips him to present a clear, evidence-based argument for the powerful influence group work has upon the opportunities for learning, and how it should therefore be an integral part of language lessons.